Public Value Subsidi Transportasi: Evaluasi Aksesibilitas dan Kepuasan Pengguna Apel Gratis di Kabupaten Bojonegoro - Nandina Salsabilla; Muhammad Miftahul Huda; Ida Swasanti (Jurnal Ragam Pengabdian, 2026)
This study evaluates the public value of the Free Student Transportation Program (APEL Gratis) implemented by the Government of Bojonegoro Regency as a transportation subsidy policy to support equitable access to education. Public transportation plays a strategic role in ensuring students’ safety, accessibility, and affordability, particularly for those living in rural and peripheral areas. This research aims to assess the extent to which APEL Gratis creates public value by examining accessibility, user satisfaction, public support, and operational capacity. The study employs a descriptive qualitative approach using in-depth interviews, field observations, and documentation. Informants were selected through purposive sampling and included student users, parents, drivers, and officials from the Department of Transportation. Data were analyzed using Miles and Huberman’s interactive model and interpreted through the Public Value Theory framework proposed by Mark H. Moore, focusing on public value, legitimacy and support, and operational capacity. The findings indicate that APEL Gratis provides tangible benefits by improving student safety, reducing transportation costs, and facilitating school access. The program has gained strong public legitimacy and support from students, parents, and schools. However, challenges remain in terms of limited route coverage, insufficient fleet capacity, and passenger overcrowding during peak hours, which affect service comfort and equity of access. Overall, APEL Gratis has succeeded in creating public value, although improvements in operational capacity are necessary to optimize service quality and ensure more equitable coverage across Bojonegoro Regency.